2014
DOI: 10.1563/aaid-joi-d-11-00196
|View full text |Cite
|
Sign up to set email alerts
|

Piezosurgery Applied to Implant Dentistry: Clinical and Biological Aspects

Abstract: Piezosurgery is a new and modern technique of bone surgery in implantology. Selective cutting is possible for different ultrasonic frequencies acting only in hard tissues (mineralized), saving vital anatomical structures. With the piezoelectric osteotomy technique, receptor site preparation for implants, autogenous bone graft acquistition (particles and blocks), osteotomy for alveolar bone crest expansion, maxillary sinus lifting, and dental implant removal can be performed accurately and safely, providing exc… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

4
46
1
4

Year Published

2015
2015
2023
2023

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 72 publications
(55 citation statements)
references
References 30 publications
4
46
1
4
Order By: Relevance
“…Its atraumatic manipulation of tissues and precision in surgery are widely accepted by oral and maxillofacial surgeons. [10] Thus, we modified the conventional approach under the help of piezosurgery, which used a bone flap with mucoperiosteal pedicle—“trapdoor” method—to restore premaxilla integrity.…”
Section: Introductionmentioning
confidence: 99%
“…Its atraumatic manipulation of tissues and precision in surgery are widely accepted by oral and maxillofacial surgeons. [10] Thus, we modified the conventional approach under the help of piezosurgery, which used a bone flap with mucoperiosteal pedicle—“trapdoor” method—to restore premaxilla integrity.…”
Section: Introductionmentioning
confidence: 99%
“…Therefore, to ensure the reliability of our findings, all the tests were performed on standardised bone samples. Previous studies [10][11][12][13][14] showed that the ultrasonic system takes more time to perforate the bone when compared with the conventional system. This can be associated with the time of frictional force of the active tips during the osteotomies 15 .…”
Section: Discussionmentioning
confidence: 99%
“…Despite the evolution of these instruments and the development of new techniques and materials, bone trauma is ever-present and the use of these instruments can cause damage to the bone tissue due to overheating during the surgical procedure and may increase the intensity of the inflammatory response. Piezoelectric surgery, which is a high-frequency surgical ultrasound system, has been advocated for carrying out precise, less invasive surgical procedures, the main advantages being the selective cutting of hard tissue and preservation of the soft tissue, less vibration and noise, absence of trauma in adjacent tissue, reduction in bleeding and an excellent view of the operative field 1 . Many studies have been published regarding osteotomies performed using piezoelectric instruments for the extraction of third molars [2][3][4][5][6] , in various categories of oral and maxillofacial surgery [7][8][9][10][11] and even in orthodontic microsurgery 12 .…”
Section: Introductionmentioning
confidence: 99%